Chemical constituents from Phlomis bovei Noë and their chemotaxonomic significance. (August 2020) - Khitri, Walid; Smati, Dalila; Mitaine-Offer, Anne-Claire; Paululat, Thomas; Lacaille-Dubois, Marie-Aleth
Abstract: A phytochemical investigation of the leaves and roots of Phlomis bovei Noë (Lamiaceae) led to the isolation of sixteen compounds, including iridoids (1, 2, 3), megastigmanes (4, 5), phenylpropanoids (6, 7, 8, 9, 10 ), lignans (11, 12, 13, 14 ), a nortriterpene (15 ), and a phenyl glucoside (16 ). Compounds (1, 2, 4, 5, 6, 10 ) were obtained from the leaves and compounds (1, 2, 3, 7, 8, 9, 11, 12, 13, 14, 15, 16 ) were isolated from the roots. Compounds 1 and 2 were found both in the leaves and in roots. The compounds were identified by analysis of 1D- ( 1 H, 13 C), 2D-NMR ( 1 H– 1 H COSY, TOCSY, ROESY, HSQC, HMBC) spectroscopic data, mass spectrometry (ESI- and HR-ESI-MS), and by comparison with previously reported spectral data. Compounds 5, 9, 10, 13 and 14 were isolated from the genus Phlomis for the first time. All these specialized metabolites were described here for the first time in the Algerian Phlomis bovei Noë species. To the best of our knowledge, no reports have appeared on the constituents of the roots of P.bovei Noë. The chemotaxonomic significance of these compounds was summarized. Graphical abstract: Image 1 Highlights: Sixteen specialized metabolites were isolated from Phlomis bovei Noë (Lamiaceae). They were characterized by NMR and mass spectroscopic methods. The chemotaxonomic significance is summarized.